1996
DOI: 10.1021/jp952864q
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of Zeolite Y as a Cracking Catalyst with the Use of Periodic Charge Equilibration

Abstract: Periodic charge equilibration (PQEq) is used to study a few of the roles that the zeolite Y lattice might play in cracking catalysis. Comparison of the partial charge distributions of HY and Na 1 HY suggests that atoms within 10 Å of the sodium atom accept electrons from the sodium atom. The charge distributions of n-octane, benzene, and water adsorbed inside the supercage of zeolite Y and siliceous zeolite Y show that the lattice provides little perturbation to these molecules. In contrast, a local dipole in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 83 publications
1
67
0
Order By: Relevance
“…Also, it was noted that a strong electron delocalization occurred: the limitation of the zeolite catalyst to a molecular fragment is then biased. This is according to Ramachandran et al 53 the main reason why associative reaction mechanisms rather than consecutive reaction mechanisms are usually more likely in zeolite. Of course, one cannot find this when doing quantum chemical calculations employing the cluster approach of these reactions, as the zeolite catalyst cavity is not explicitly considered.…”
Section: Discussionmentioning
confidence: 77%
“…Also, it was noted that a strong electron delocalization occurred: the limitation of the zeolite catalyst to a molecular fragment is then biased. This is according to Ramachandran et al 53 the main reason why associative reaction mechanisms rather than consecutive reaction mechanisms are usually more likely in zeolite. Of course, one cannot find this when doing quantum chemical calculations employing the cluster approach of these reactions, as the zeolite catalyst cavity is not explicitly considered.…”
Section: Discussionmentioning
confidence: 77%
“…Ramachandran et al created the periodic charge equilibration (PQEq) method to derive the charges for periodic systems. 879 They applied the method to systems related to zeolite Y and found that the zeolite lattice has little influence on the charge distributions of absorbed n -octane, water, and benzene, but a considerable effect on the charge distribution of the transition state in the hydride transfer reaction between the C 4 H 9 + ion and n -octane.…”
Section: Classical Modeling Of Metal Ions: the Polarizable Modelmentioning
confidence: 99%
“…Ramachandran et al extended the original approach to the extended crystals by incorporating the lattice effect in the expression for the chemical potential and called it the periodic charge equilibration method (PQeq). 42 Haldoupis et al adapted these methods for use with MOFs. 12 The charge assignment methods outlined above rely on the assumption that assigning point charges to MOF atoms is sufficient to reproduce the electrostatic interaction relevant to adsorbing molecules.…”
Section: Introductionmentioning
confidence: 99%